Signal-dependent regulation of splicing via phosphorylation of Sam68 - Matter, Nathalie; Herrlich, Peter; König, Harald (Nature (London), 2002)
Evolution of human organismal complexity from a relatively small number of genes 1 , 2 —only approximately twice that of worm or fly—is explained mainly by mechanisms generating multiple proteins from a single gene, the most prevalent of which is alternative pre-messenger-RNA splicing 1 , 3 , 4 . Appropriate spatial and temporal generation of splice variants demands that alternative splicing be subject to extensive regulation, similar to transcriptional control. Activation by extracellular cues of several cellular signalling pathways can indeed regulate alternative splicing 5 , 6 , 7 , 8 . Here we address the link between signal transduction and splice regulation. We show that the nuclear RNA-binding protein Sam68 is a new extracellular signal-regulated kinase (ERK) target. It binds exonic splice-regulatory elements of an alternatively spliced exon that is physiologically regulated by the Ras signalling pathway, namely exon v5 of CD44. Forced expression of Sam68 enhanced ERK-mediated inclusion of the v5-exon sequence in mRNA. This enhancement was impaired by mutation of ERK-phosphorylation sites in Sam68, whereas ERK phosphorylation of Sam68 stimulated splicing of the v5 exon in vitro . Finally, Ras-pathway-induced alternative splicing of the endogenous CD44-v5 exon was abolished by suppression of Sam68 expression. Our data define Sam68 as a prototype regulator of alternative splicing whose function depends on protein modification in response to extracellular cues.